A STUDY ON THE EXISTENTIALISM AND ITS RELEVANCE TO THE READING LEARNING FOR ELEMENTARY SCHOOL STUDENTS - Kurniaman, Otang; Copriady, Jimmi; Firdaus, L.N (PD PGMI se Indonesia, 2023)
This article discusses the description of a study on existentialism in which its relevance to the reading learning is seen based on the teaching and learning procedures applied by the teacher in order to make a more qualified teaching and learning process for students who have rights and obligations. The research method used is a qualitative approach with descriptive method that focused on a philosophical study (Rahman, 2020) with a library research method or literature review by analyzing one book entitled Model-Model Pembelajaran Bahasa Indonesia di SD/MI written by Siti Anisatun Nafiah (2018) and published by Ar-Ruzz Media in Yogyakarta. Humans did not only live throughout their lives in themselves, and they were in the human realm, but they also went out of themselves to pursue a transcendent goal so that humans could make up their existence for themselves. In this relation, every learning subject in elementary school should prioritize the essence for students as Gods Creature who have different abilities in the reading learning. Existentialism view on the reading learning that imparted a number of opinions emphasized that it was no need the more freedom rules in the reading learning. On this occasion, the students and the teachers are the subjects who recognized the time. Past, future and present times are similar for them. Students as individuals have chosen their lives based on their volition. It means that students can find out the real meaning of life if they can relate to their selves to do unlimited actions and be ready to contemplate a life even though they realized they have limited to do it.